(untitled) (Research, Society and Development, 2021)
Chronic kidney disease (CKD) and its complications have a major impact on the quality of life of affected patients, and may lead to death. The neutrophil-lymphocyte ratio (NLR), lymphocyte-monocyte ratio (LMR), platelet-lymphocyte ratio (PLR) and mean platelet volume (MPV) can be used as prognostic determinants of patients in various clinical situations. The aim of this review was to search the literature for evidence about cellular ratios (NLR, LMR, PLR and MPV) and their correlation with CKD. To this end, an integrative literature review was carried out in LILACS, MEDLINE, PubMed, and CINAHL databases of productions from the last 10 years. The descriptors used were: "chronic kidney disease", "chronic kidney injury", "chronic renal failure", "monocyte to lymphocyte ratio", "monocyte to lymphocyte ratio", "neutrophil to lymphocyte ratio", and "neutrophil to lymphocyte ratio", which were combined to delimit the search. Twenty-six articles were selected at the end of the search steps. Being the year 2019 the most prevalent with 19.23% of publications, followed by the year 2013 and 2016 with 15.38% of publications. Regarding the country of origin of the studies, 53.8% were conducted in Turkey, followed by studies conducted in China with 15.38% and the United States, Taiwan and Japan with 7.69% in each country . Most studies presented data showing that cellular ratios such as MRL, PLR, MPV and especially NRL are practical tools and can be used as markers of systemic inflammation and predictors of morbidity and mortality in CKD, especially those patients with end-stage disease. Therefore, it was evidenced that there is an increase in cellular ratios in CKD patients. Moreover, this is a cost-effective method to predict inflammation and mortality. However, further studies are needed to expand its use in clinical practice.